2018
DOI: 10.1002/hed.25583
|View full text |Cite
|
Sign up to set email alerts
|

High pretreatment neutrophil‐to‐lymphocyte ratio as a predictor of poor survival prognosis in head and neck squamous cell carcinoma: Systematic review and meta‐analysis

Abstract: Background The prognostic roles of neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) have been reported in head and neck squamous cell carcinoma (HNSCC), but their results remain controversial. Methods A total of 25 literatures with 28 cohorts involving 6847 HNSCC patients were included. The hazard ratio (HR) was pooled with 95% confidence interval (CI) using fixed‐effects or random‐effects models. Results High pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 61 publications
(103 reference statements)
1
67
0
2
Order By: Relevance
“…Tumour inflammatory microenvironments are complex and dynamic, involving crosstalk between various immune cells and tumour cells. Inflammatory prognostic scores such as the NLR, PLR, and LMR calculated using immune cellrelated values have shown promise in various tumour types [16][17][18][19]. In addition, the efficacy of the SIRI has been reported in limited types of cancer, such as liver [20], pancreatic [3], gastric [4], and nasopharyngeal [5] cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour inflammatory microenvironments are complex and dynamic, involving crosstalk between various immune cells and tumour cells. Inflammatory prognostic scores such as the NLR, PLR, and LMR calculated using immune cellrelated values have shown promise in various tumour types [16][17][18][19]. In addition, the efficacy of the SIRI has been reported in limited types of cancer, such as liver [20], pancreatic [3], gastric [4], and nasopharyngeal [5] cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most of the included studies on the prognostic role of the NLR and PLR were performed in Asians, thus, the results about non-Asians should be interpreted cautiously and need to be validated further. Additionally, despite the lack of standardized cut-off values, most of the studies were performed using cut-off levels ranging from 1.62 to 5 for the NLR and 81.62 to 300 for the PLR [40].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis (Yang, Huang, Zhou, Dai, & Hu, 2019) confirmed that NLR ratio is also a prognostic marker in OPC for disease-free survival (DFS) and overall survival (OS).…”
Section: Introductionmentioning
confidence: 97%